THE EFFECT OF WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. AQIQAH86 SOUTH TANGERANG - Ading Sunarto; Nindie Ellesia (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of work environment and work discipline on employee performance at PT.Aqiqah86 Tangerang Selatan, either partially or simultaneously. The method used is descriptive with an associative approach. At the same time, obtaining data is done by distributing questionnaires to 60 company respondents who then analyzed the effect partially and simultaneously using regression analysis, coefficient of determination, and hypothesis testing with t-test and F-test. Employee Performance, For the partial hypothesis test results obtained by the value of t count > t table (8.675 > 1.669), it can be concluded that Ha1 is accepted, or the Work Environment variable (X1) partially has a positive and significant effect on Employee Performance (Y). The Effect of Work Discipline on Employee Performance, for the partial hypothesis test results obtained by the value of tcount,> ttable (8.165 > 1.669), it can conclude that Ha2 is accepted or the Work Discipline variable (X2) partially has a positive and significant effect on Employee Performance (Y). The results obtained are Farithmetic = 49,472 > 3.15 or (Farithmetic > Ftable) so that Ho3 is rejected and Ha3 is accepted. It means that there is a positive and simultaneous influence between Work Environment and Work Discipline on Employee Performance at PT. Aqiqah86 Tangerang Selatan